2019
DOI: 10.1002/ppul.24360
|View full text |Cite
|
Sign up to set email alerts
|

Lung function in children with juvenile idiopathic arthritis: A cross‐sectional analysis

Abstract: Aim We measured respiratory parameters in children with juvenile idiopathic arthritis (JIA) without clinical signs of respiratory involvement and assessed the influence of methotrexate (MTX) treatment and disease activity on lung function. Methods In 49 JIA children and 70 controls lung volumes by spirometry and body plethysmography, and lung diffusion for carbon monoxide (DLCO) with single‐breath technique were evaluated. Results DLCO was significantly different between JIA children and controls (P = .01), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…Many disease-modifying antirheumatic drugs have been reported to cause pulmonary toxicity, such as drug-induced ILD, in many case reports and retrospective studies [ 26 ]. Attanasi et al found a negative correlation of DL CO with cumulative methotrexate (MTX) dosage and the duration of MTX treatment in one study on JIA [ 8 ]. All patients in our study were treatment-naive and newly diagnosed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many disease-modifying antirheumatic drugs have been reported to cause pulmonary toxicity, such as drug-induced ILD, in many case reports and retrospective studies [ 26 ]. Attanasi et al found a negative correlation of DL CO with cumulative methotrexate (MTX) dosage and the duration of MTX treatment in one study on JIA [ 8 ]. All patients in our study were treatment-naive and newly diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…DL CO is the most sensitive test for predicting the presence of ILD [ 32 ], and a reduction in DL CO suggests abnormalities of the alveolar–capillary interface, compatible with diffuse vascular and/or parenchymal lung disease [ 8 ]. The significant increase in FEV1/FVC and respiratory rate compared with that of controls may reflect volume loss associated with fibrosis, although FVC and FEV1 remained within the normal range after the decline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, screening techniques for subclinical disease are required. Indeed, lung function assessment could be useful in patients with JIA to improve patient management and to detect early pulmonary involvement [ 52 ]. Moreover, sJIA-LD may have been present since a patient was 2 years of age as children are unable to perform the recommended screening tests for sJIA-LD, including the 6-minute walk test, the lung function tests or an unsedated HRCT.…”
Section: Diagnostic Imagingmentioning
confidence: 99%
“…Although lung involvement is well-described among adults with rheumatoid arthritis, 42 data describing pulmonary manifestations of juvenile idiopathic arthritis (JIA) are sparse. [43][44][45] Attanasi et al 46 studied spirometry, body plethysmography, and diffusion capacity results in 49 children with JIA and compared them to the same from 70 unaffected controls. Only D L CO was lower in the JIA patients, and it was correlated with active disease.…”
Section: Children's Interstitial Lung Disease (Child) Disordersmentioning
confidence: 99%